The Evaluation of Iranian midwifery Ph.D. course based on the CIPP model - Robab Hasanzadeh; Solmaz Ghanbari Homaie; Sakineh Mohammad-Al; Mina Iravani; Saiedeh sadat Hajimirzaie; Shahla Khosravi; Parvin Abedi; Mojgan Mirghafourvand (Mashhad University of Medical Sciences, 2023)
Background: A high-quality Ph.D. course requires frequent assessment and identification of deficiencies and limitations. The midwifery Ph.D. course started in 2016 in Iran and since no evaluation has been performed on this program, the present study aimed to evaluate the Iranian midwifery Ph.D. course based on the CIPP model.Method: This descriptive-evaluative research was conducted based on the CIPP model in 2021 in the schools of nursing and midwifery of Tabriz and Ahvaz Universities of medical sciences, Iran. The statistical population included the faculty members of the midwifery Ph.D. program (9 individuals) and midwifery Ph.D. graduates and students (21 individuals). The data collection tools comprised CIPP-based questionnaires exclusively for faculty members and students. Descriptive statistics were employed for data analysis.Results: Most students (81%) and faculty members (77.8%) reported an appropriate general evaluation of the midwifery Ph.D. curriculum. Most faculty members (77.8%) and students (90.8%) reported the indicators of the midwifery Ph.D. curriculum as appropriate in terms of context. More than three forth of faculty members (77.8%) and more than half of the students (57.1%) reported this curriculum as appropriate regarding input. This program was also reported to be appropriate according to 52.4% of students and 66.7% of faculty members in terms of process. Furthermore, a total of 66.7% of participants in both groups reported an appropriate status in terms of output.Conclusion: Midwifery Ph.D. curriculum was reported as an appropriate program. Also, students of this discipline requested greater stress on clinical upskilling for midwifery Ph.D.